L’inventaire des objets mobiliers religieux des XIXe et XXe siècles : méthodologie - Laurence de Finance (In Situ)
The religious furnishings and artefacts of the 19th century are studied in France in course of the topographical inquiries carried out by the general inventory services in the regions. Selection criteria established in the 1990s provide guidelines for the research teams as to what was worth selecting for documentation as unique objects, possibly worthy of statutory protection, and what could be simply documented using core data (fiche minimum). But the same criteria are not necessarily applicable to the religious furnishings and artefacts of the 20th century, and after 1920 in particular. New notions to do with the fragility of the material with which the work is made, making the objects ephemeral, the creation of the object and its particular aesthetics are perhaps to be taken into account where the religious objects of the second half of the 20th century are concerned. The documentary notices included in the Palissy database should also be capable of reflecting the impact of the Vatican II Council and the novelties of the 1960s and 1970s.